2018
DOI: 10.1111/cns.13082
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid beta soluble forms and plasminogen activation system in Alzheimer’s disease: Consequences on extracellular maturation of brain‐derived neurotrophic factor and therapeutic implications

Abstract: Summary Soluble oligomeric forms of amyloid beta (Aβ) play an important role in causing the cognitive deficits in Alzheimer’s disease (AD) by targeting and disrupting synaptic pathways. Thus, the present research is directed toward identifying the neuronal pathways targeted by soluble forms and, accordingly, develops alternative therapeutic strategies. The neurotrophin brain‐derived neurotrophic factor (BDNF) is synthesized as a precursor (pro‐BDNF) which is cleaved extracellularly by plasmin to rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 130 publications
(250 reference statements)
1
33
1
Order By: Relevance
“…A direct consequence of the glymphatic system disturbance is the reduced clearance of neurotoxic substances, such as beta amyloid (Aβ) and hyperphosphorylated tau (HP tau) 53,87 . Accumulation of these neurotoxic substances could not only impair physiological functions of neurons, but also trigger astrogliosis and neuroinflammation 96 . Several studies reported the aggregation of Aβ and HP tau in brain biopsy samples from iNPH patients 97 .…”
Section: Glymphatic Impairment Increases Brain Damage In Inphmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct consequence of the glymphatic system disturbance is the reduced clearance of neurotoxic substances, such as beta amyloid (Aβ) and hyperphosphorylated tau (HP tau) 53,87 . Accumulation of these neurotoxic substances could not only impair physiological functions of neurons, but also trigger astrogliosis and neuroinflammation 96 . Several studies reported the aggregation of Aβ and HP tau in brain biopsy samples from iNPH patients 97 .…”
Section: Glymphatic Impairment Increases Brain Damage In Inphmentioning
confidence: 99%
“…DTI‐MRI is another useful technique to assess the white matter lesion. Mean diffusivity (MD) and fractional anisotropy (FA) are two commonly analyzed DTI parameters 96 . MD increases when more free water diffuses in the extracellular space.…”
Section: White Matter Injury In Inphmentioning
confidence: 99%
“…The tissue plasminogen activator (tPA)/plasmin system has been suggested as a therapeutic target for AD (Angelucci et al, 2019). Plasmin can cleave Aβ and Aβ deposits, suggesting that it may be involved in Aβ clearance (Ledesma et al, 2000;Jacobsen et al, 2008;Baranello et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among these compounds, (E)-5-(4hydroxystyryl) quinoline-8-ol showed the most potent ability to inhibit selfinduced Aβ aggregation (IC50 = 8.50 μM) and copper(II)-induced Aβ aggregation and to disassemble the well-structured Aβ fibrils generated by self-and copper(II)-induced Aβ aggregation ( Figure 2) (Mao et al, 2014b). Previously it has been shown that molecular deletion of plasminogen activator inhibitor 1 PAI-1 significantly reduced brain Aβ load in animal model (Angelucci et al, 2019). In this regard, oral administration of TM5275, a small molecule inhibitor of PAI-1, has been indicated to reduce A β load in the hippocampus and consequently improve memory function in animal model (Akhter et al, 2018).…”
Section: Figurementioning
confidence: 91%